Strategic Planning and Policy Making for Tourism Development in Cyprus: An Empirical Case-based Approach - Saveriades, Alexis (My University, 2023)
Chapter 1 deploys a critical approach to examine all plans that have been put into force on the Island of Cyprus since its inauguration in 1960. By identifying tourism planning as an integral part of a destination’s development strategy, Saveriades unfolds and critically analyzes the tourism plans in an attempt to foresee the future of the destination through its past and endeavors.
Keywords: Strategic planning; Policy making; Tourism development; Tourism governance